Tools to Study SUMO Conjugation in Caenorhabditis elegans - Pelisch, Federico Gaston (2016)
The cell biology of sumoylation has mostly been studied using transformed cultured cells and yeast. Inrecent years, genetic analysis has demonstrated important roles for sumoylation in the biology of C. elegans. Here, we expand the existing set of tools making it possible to address the role of sumoylation in thenematode C. elegans using a combination of genetics, imaging, and biochemistry. Most importantly, thedynamics of SUMO conjugation and deconjugation can be followed very precisely both in space and timewithin living worms. Additionally, the biochemistry of SUMO conjugation and deconjugation can beaddressed using recombinant purifi ed components of the C. elegans sumoylation machinery, including E3ligases and SUMO proteases. These tools and reagents will be useful to gain insights into the biologicalrole of SUMO in the context of a multicellular organism.